Applications of catalysis in hydroboration of imines, nitriles, and carbodiimides. Issue 18 (22nd April 2022) - Rezaei Bazkiaei, Adineh; Findlater, Michael; Gorden, Anne E. V.
Abstract : Catalytic hydroboration of imines, nitriles, and carbodiimides are reviewed as powerful tools for preparation of amines. Abstract : The catalytic hydroboration of imines, nitriles, and carbodiimides is a powerful method of preparing amines which are key synthetic intermediates in the synthesis of many value-added products. Imine hydroboration has perennially featured in notable reports while nitrile and carbodiimide hydroboration have gained attention recently. Initial developments in catalytic hydroboration of imines and nitriles employed precious metals and typically required harsh reaction conditions. More recent advances have shifted toward the use of base metal and main group element catalysis and milder reaction conditions. In this survey, we review metal and nonmetal catalyzed hydroboration of these unsaturated organic molecules and group them into three distinct categories: precious metals, base metals, and main group catalysts. The TON and TOF of imine hydroboration catalysts are reported and summarized with a brief overview of recent advances in the field. Mechanistic and kinetic studies of some of these protocols are also presented.